Lewis acidic FeCl3 promoted 2-aza-Cope rearrangement to afford α-substituted homoallylamines in dimethyl carbonate. Issue 31 (7th June 2019) - Gadde, Karthik; Daelemans, Jonas; Maes, Bert U. W.; Abbaspour Tehrani, Kourosch
Abstract : The current work shows an iron-catalyzed 2-aza-Cope rearrangement in dimethyl carbonate for the synthesis of a wide variety of α-substituted homoallylamines from readily accessible starting materials with diverse functional groups. Abstract : The iron(iii )-catalyzed efficient strategy for the synthesis of α-substituted homoallylamines was accomplished via a cationic 2-aza-Cope rearrangement of aldimines, generated in situ by condensation of commercially available aldehydes and easily synthesizable 1, 1-diphenylhomoallylamines. This reaction features a broad substrate scope with high yields and is conducted in an eco-friendly solvent, i.e. dimethyl carbonate.